Studi Korelasional Nilai Matematika terhadap Nilai Fisika Siswa Kelas XI pada Implementasi Pendekatan Deep Learning di SMAN 10 Mataram - Khaira Ulfa; Wahyudi; I Wayan Gunada (Mataram University, 2026)
This study aimed to examine the relationship between mathematics and physics achievement scores among eleventh-grade students at SMAN 10 Mataram. The research employed a quantitative approach using a correlational research design. Saturated sampling was applied to select 58 students from class XI Science as the research subjects. The data source consisted of students’ end-of-semester summative scores in mathematics and physics. Data analysis was conducted using SPSS 25 through the Kolmogorov-Smirnov normality test, linearity test, and Spearman’s Rho correlation test. The descriptive analysis results showed that the average mathematics score was 82.127 with a standard deviation of 4.193, while the average physics score was 82.131 with a standard deviation of 2.521. The normality test indicated that the data were not normally distributed; therefore, the hypothesis testing was conducted using Spearman’s Rho correlation analysis. The correlation test results revealed a correlation coefficient of 0.490 with a significance value of 0.000. These findings indicate a positive and significant relationship between mathematics and physics achievement scores with a moderate level of correlation. Thus, mathematical ability plays an important role in supporting students’ physics learning achievement, particularly in deep learning-based instruction that emphasizes conceptual understanding, quantitative reasoning, and problem-solving skills.